Land Use Modification and Changing Redox Conditions Releases Selenium and Sulfur from Historic Marsh Sediments. (5th September 2017) - Hibbs, Barry J.; Lee, Monica; Ridgway, Rachel
Abstract: San Diego Creek Watershed forms the southern end of the Coastal Plain that covers much of Los Angeles County and Orange County, California. Prior to 1900, the central part of the watershed was marshland, and the edges of the watershed were used for grazing sheep and cattle. After 1900, cattle and sheep grazing were displaced by irrigated agriculture. Drainage ditches and channels were constructed to drain the marshes to "reclaim" the land for agriculture. Today, the drainage ditches and channels still exist in the watershed, which has undergone massive urban growth. Shallow groundwater discharges into these channels and ditches, which then flows as surface water, into Upper Newport Bay a thriving ecological habitat. Surface flows in these channels usually exceed the United States Environmental Protection Agency (EPA) aquatic water quality criterion for selenium (Se) of 3.1 μg/L (lotic) for protection of aquatic life. Selenium in surface flows is caused by groundwater inflows. The highest concentrations of Se in shallow groundwater in the watershed coincide with the marshland area that was displaced by agriculture. Concentrations of Se in shallow groundwater beneath the former marsh area often exceed 25 μg/L and are as high as 478 μg/L. In areas where marshes were absent, concentrations of Se in groundwater are usually less than 25 μg/L. In the marsh, Se accumulated due to chemically reducing conditions in the organic‐rich marshland soils that caused it to precipitate as elemental Se(0) and metal selenides, Se(−II). We hypothesize that the elevated concentrations of Se in groundwater where the marshes once existed are a direct result of the destruction of the marsh. Today, oxidizing groundwater flows through the soils where the marshes once existed, remobilizing Se as selenate, a water soluble and oxidized form of Se(+VI) that is highly mobile in aquifer systems.